Turkish State Criminality against Kurds and Victimization through Impunity. (8th November 2022) - Karakas, Sanya
Abstract : This article explores the long-lasting effects of impunity on victims' everyday lives. Drawing on Rojas Baeza's medico-psychiatric definition of impunity, the article discusses how impunity creates different traumatic consequences in a victim's life and prolongs the suffering of victims and their families. The article argues that the absence of justice, the denial of truth, and non-accountability of perpetrators of state crimes, not only constitute significant components of the mechanics of impunity but also create eventual and painful effects in victims' daily lives. The article uses primary data from my field research conducted in Turkey, and exemplifies some of the traumatic consequences of state crimes committed by the Turkish state against Kurds and their eventual effects on the victims' lives. The article examines these long-term effects of impunity on victims to develop the concept of victimization in the context of state crimes and impunity.